DOI: 10.31274/rtd-180813-9541
|View full text |Cite
|
Sign up to set email alerts
|

Teacher perceptions of agricultural teaching practices and methods for youth and adults in Iowa

Abstract: Teaching/learning process 28 Method of teaching youth 33 Method of teaching adults 35 CHAPER ni. METHODS OF PROCEDURE Assumptions 38 Limitations Definition of terms Research design Development of mailed questionnaire Determining the target population Selection of sample Data collection Analysis of data CHAPTER IV. FINDINGS Respondent's perceptions of the importance of selected teaching techniques Respondent's perceptions of the importance of selected teacher's characteristics Teachers perceptions of the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
3
0
3
Order By: Relevance
“…The significance of this study is related to the present and future of agricultural education and to understanding and improving the use of the principles of teaching-learning, methods and tools and their effectiveness. To improve the quality of teaching and learning that accommodates the needs and preferences of agricultural learners it is necessary to study the educational delivery system (Moore, 1995;Dyer et al, 1995;Kassem, 1992). Some authors (Moore, 1995;Kahler, 1995) have suggested that instruction in secondary agricultural education has been inadequately delivered or did not meet educational needs.…”
Section: Implications and Educational Significancementioning
confidence: 99%
See 2 more Smart Citations
“…The significance of this study is related to the present and future of agricultural education and to understanding and improving the use of the principles of teaching-learning, methods and tools and their effectiveness. To improve the quality of teaching and learning that accommodates the needs and preferences of agricultural learners it is necessary to study the educational delivery system (Moore, 1995;Dyer et al, 1995;Kassem, 1992). Some authors (Moore, 1995;Kahler, 1995) have suggested that instruction in secondary agricultural education has been inadequately delivered or did not meet educational needs.…”
Section: Implications and Educational Significancementioning
confidence: 99%
“…Newcomb et al (1986, p. 6) stated that "instruction in agriculture varies depending on the level at which instruction is provided and the persons for whom the instruction is offered." A recent study entitled "Teacher perceptions of agricultural teaching practices and methods for youth and adults in Iowa" (Kassem, 1992) concluded that the most important thing in teaching agriculture is the need for the agriculture teacher to use effective methods and preparation for teaching.…”
Section: Chapter L Introduction Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Ito ay tumutukoy bilang mga gawain ng guro sa klase na nanghihikayat sa mga mag-aaral na makilahok sa talakayan at mga aktibidad sa pagkatuto na pantay-pantay na nakibahagi sa iba at nagbigay-puna sa pagkatutong naranasan Finlay (2017). Kailangan din ng guro na gumanap bilang kaibigan ng mga mag-aaral, gawing mas kumportable ang lugar ng pagkatuto, magkaroon ng mabisang banghay-aralin, at magbigay ng impluwensiya sa mga mag-aaral gamit ang iba't ibang pamamaraan ng pagtuturo (Kassem, 2015). Sa katunayan, ang mabisang mga guro na may mga tiyak na pamamaraan sa pagtuturo ay tiningnan bilang mga eksperto sa pamamahala sa silid-aralan Harper (2015).…”
Section: Pangangasiwang Pangklasrumunclassified
“…Ang ikatlong indikeytor ay pakikipagsapalaran. Ito'y tumutukoy sa anumang kontrolado o di-kontroladong pag-uugali na mapupuna ang walang katiyakang kahihinatnan ukol sa posibleng pakinabang at kapakanan ng sarili o ng kapwa Kassem (2015). Ang pakikipagsapalaran ay maaaring di-katanggap-tanggap na kagustuhang pag-uugaling panlipunan na may posibleng negatibong kalalabasan dahil sa hindi isinaalang-alang ang pag-iingat (Trimpop, 2015;Turner at Patrick, 2015).…”
Section: International Journal Of Research Studies In Education 165unclassified